Influenced of Self-Help Group towards Self-Management and Quality of Life among Older Adults With Chronic Non-communicable Disease in Malang - Niko Dima Kristianingrum; Cornelia Fransiska Sandehang; Afiatur Rohimah; Zaroan Supriadi; Agung Prasetia; Annisa Wuri Kartika; Yati Sri Hayati; Kumboyono Kumboyono; Dina Dewi Sartika Lestari Ismail; Dian Handayani; Lilik Zuhriyah (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
The increasing of older adults population concomitant with the increasing of chronic non-communicable diseases. Chronic non-communicable diseases can have an impact on the quality of life of the older adults. Chronic non-communicable diseases require long-term management through self-management. This study aimed to analyze the Self Help Group (SHG) intervention towards self-management and quality of life for older adults with chronic non-communicable diseases. The research method was Quasi Experimental pre-post test with control group on 120 respondents selected by purposive sampling. The inclusion criteria were age more than 60 years, had DM or gout, communicating well, capable to read and write. The SHG intervention hold on four meetings is a group activity of fellow sufferers to share problems and experiences. The instruments were the self-management behavior questionnaire and WHOQOL-BREF. The results of the Mann Whitney test showed p=value of 0.000 which mean that there was a significant difference between self-management and quality of life in the control group and the SHG intervention group. The conclusion was that SHG influenced self-management and quality of life among older adults with chronic non-communicable diseases. Need to apply self help group regularly among chronic non-communicable disease patients. Abstrak: Peningkatan lansia seiring dengan peningkatan penyakit tidak menular kronis. Penyakit tidak menular kronis dapat berdampak pada kualitas hidup lansia. Penyakit tidak menular kronis memerlukan penatalaksanaan jangka panjang melalui manajemen diri. Tujuan penelitian ini untuk menganalisis penerapan Self Help Group (SHG) pada manajemen diri dan kualitas hidup lansia dengan penyakit tidak menular kronis. Metode penelitian adalah Quasi Exsperimental pre-post test with control group pada 120 responden yang dipilih dengan purposive sampling. Kriteria inklusi yaitu usia lebih dari 60 tahun, mengalami DM atau gout, dapat berkomunikasi, dapat membaca dan menulis. Intervensi SHG selama empat kali pertemuan merupakan kegiatan kelompok sesama penderita untuk berbagi masalah dan pengalaman. Instrumen yaitu self-management behaviour questionnaire dan WHOQOL-BREF. Hasil uji mann whitney menunjukkan p=value 0.000 yang bermakna terdapat perbedaan yang signifikan antara manajemen diri dan kualitas hidup pada pada kelompok control dan kelompok intervensi SHG. Kesimpulan yaitu adanya pengaruh SHG pada manajemen diri dan kualitas hidup lansia dengan penyakit tidak menular kronis. Perlu mengaplikasikan SHG secara teratur pada pasien dengan penyakit tidak menular kronis.